Chaperone-mediated autophagy dysfunction in imiquimod-induced psoriasiform dermatitis - Wei Zhao; Kainan Liao; Wei Song; Jing Wang; Chunlin Cai; Fusheng Zhou; Dandan Zang; Deping Xu; Haisheng Zhou (Autophagy Reports)
Psoriasis is a chronic inflammatory skin disease characterized by abnormal differentiation and hyperproliferation of epidermal keratinocytes. Autophagy plays a critical role in regulating the functions of immune cells, endothelial cells, and especially keratinocytes, contributing to the pathogenesis of psoriasis. However, the role of chaperone-mediated autophagy (CMA) in psoriatic keratinocytes has not been fully explored. Our study, for the first time, revealed that defective CMA is present in imiquimod (IMQ)-induced psoriasiform lesions. Importantly, activation of CMA significantly attenuated IMQ-induced phenotypes both in vitro and in vivo, including reduced skin lesion severity, decreased keratinocyte proliferation and differentiation, and lower cytokine secretion. Mechanistically, toll-like receptor 7 (TLR7), containing a specific KFERQ-like motif, is a substrate for CMA-mediated degradation. This process modulates IMQ-TLR7 signal activation in keratinocytes. CMA deficiency in psoriasis leads to increased TLR7 levels, which, in turn, enhances TLR7-NF-κB signaling pathway activation, ultimately contributing to dysregulated keratinocyte proliferation, differentiation, and cytokine secretion. This study provides novel evidence that defective CMA is present in IMQ-induced psoriasiform lesions and that CMA activation can attenuate IMQ-induced phenotypes by modulating TLR7 signaling in keratinocytes. These findings highlight the potential of CMA as a therapeutic target for psoriasis.